(untitled) (Research, Society and Development, 2025)
The general objective that guided this study was formulated as follows: to present a case report on sodium valproate intoxication in pediatrics. Accordingly, the specific objectives were defined in three topics: (1) to understand the patient’s clinical evolution related to this type of intoxication, from admission to the end of treatment in this institution; (2) to analyze the clinical complications resulting from this condition; and (3) to analyze the treatments proposed in the literature for intoxication caused by this drug. In general, this medication is classified as an anticonvulsant, used in cases of epilepsy and bipolar disorder, and sodium valproate is widely associated with intoxications, whether intentional or unintentional. Its main adverse effects include central nervous system depression, hepatotoxicity, electrolyte disturbances, and cardiac rhythm abnormalities, and it is rapidly absorbed through the gastrointestinal tract. The present case report addressed the patient A.R.S., aged 4 years and 3 months, referred from an urgent care unit on January 29, 2025, with a clinical presentation of exogenous intoxication by VPA (500 mg per tablet, ingestion of 49 tablets) and an unknown amount of amitriptyline 50 mg. The patient was admitted to the ICU of HUMAP in critical condition and, despite all implemented interventions, progressed to death on February 6, 2025, as a consequence of the large quantity of VPA ingested. The study revealed a lack of standardized protocols in the literature to guide the management of VPA intoxications and highlights the importance of such protocols to promote a more systematic approach in the care of these cases.